United Germany : The First Five Years: Performance and Policy Issues - Habermeier, Karl (Occasional Papers; Occasional Paper ;, 1995)
This papers reviews economic and financial developments in Germany since its reunification nearly five years ago; and analyzes some critical issues that have featured prominently in the policy debate over this period and are likely to continue attracting attention in the years ahead.